Exploring Speech Acts in Online Discourse: A Study of Beta Squad Youtube Content - Pipit Anggita Wulandari; Elsan Arvian (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2026)
This research explores the use of speech acts in online discourse by analyzing Beta Squad YouTube content. The research aims to identify the types of speech acts used by Beta Squad members and examine how these speech acts function within digital interaction. This research applies Searle’s speech act theory, which classifies speech acts into five categories: assertives, directives, commissives, expressives, and declarations. A qualitative descriptive method with a discourse analysis approach was employed to analyze the utterances produced by Beta Squad members in a selected YouTube video. The data were collected through observation and documentation by transcribing relevant utterances and classifying them based on their communicative functions. The findings reveal that all five types of speech acts appear in the analyzed content. From 23 identified utterances, assertive speech acts are the most dominant category with 8 occurrences (34.7%), followed by directive and commissive speech acts with 5 occurrences each (21.7%). Expressive speech acts appear 3 times (13.0%), while declaration speech acts appear the least with 2 occurrences (8.6%). The results indicate that Beta Squad members mainly use assertive acts to provide information, express opinions, and describe situations during interaction. Directive and commissive acts are used to control the flow of communication, give instructions, and express future intentions, while expressive acts contribute to humor and social bonding among participants. This research demonstrates that speech acts in online discourse function not only as communication tools but also as social actions that create interaction, entertainment, and relationships. The findings highlight the importance of analyzing digital content to understand how language operates in contemporary online communication.